2013
DOI: 10.2478/pjvs-2013-0070
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and antimicrobial resistance of Campylobacter isolated from pig and cattle carcasses in Poland

Abstract: A total of 70 Campylobacter isolates recovered from 114 cattle and 177 pig carcasses at the slaughterhouse level were characterized by the presence of 7 putative virulence genes and antimicrobial susceptibility using the microbroth dilution method and minimal inhibitory concentration (MIC). The prevalence of Campylobacter was 14.9% and 29.9% in cattle and pig samples, respectively. The majority of cattle carcasses were contaminated with C. jejuni (64.7%), whereas pig carcasses were mainly positive for C. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
(65 reference statements)
6
20
1
Order By: Relevance
“…Among swine 8% of isolates were identified as C. jejuni and 92% as C. coli. The results obtained are in line with studies of other authors, which showed the dominance of C. jejuni in cattle and C. coli in swine (Ghafir et al 2007, Wieczorek andOsek 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among swine 8% of isolates were identified as C. jejuni and 92% as C. coli. The results obtained are in line with studies of other authors, which showed the dominance of C. jejuni in cattle and C. coli in swine (Ghafir et al 2007, Wieczorek andOsek 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The wide prevalence of Campylobacter spp. in animal population carries the risk of contamination of food products such as raw or uncooked meat, milk and water (Wieczorek and Osek 2013). Poultry and poultry meat are described as the Datta et al (2003) of toxin production is the one that plays a special role in the pathogenesis of bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…33,38,41 Furthermore, the prevalence of C. coli in this study is similar to that reported in other countries. 21,62,69,92 The distribution of C. jejuni and C. coli can be influenced by many factors, including seasonality, age of the animal, and geographical locations. For example, Sanad et al 75 reported a higher prevalence of C. coli in cattle fecal samples collected from the Southern United States in comparison to those from Northern, Midwestern, and Eastern regions.…”
Section: Discussionmentioning
confidence: 99%
“…31,[74][75][76] Furthermore, although the prevalence of Campylobacter in cattle carcasses and milk samples can be relatively low in comparison to other sources, studies have shown that approximately 15% of beef carcasses/meat can be contaminated with these pathogens. 38,92 In addition, a Campylobacter prevalence of 41.7%, 10.2%, and 4.6% had been previously reported in raw bulk tank milk in Northern Italy, Pakistan, and Poland, respectively, while 6.25% of raw cow milk samples from retail stores were contaminated with Campylobacter in Iran. 9,41,69,94 Milk can be considered a re-emerging risk factor, because the consumption of unpasteurized raw milk and/or products made from raw milk is becoming more popular in most countries.…”
mentioning
confidence: 89%
“…Studies in Nigeria [67,68] reported that ciprofloxacin was effective against all the strains of Campylobacter tested. Many other studies have revealed variability in proportions of resistant Campylobacter isolates to ciprofloxacin and erythromycin [57,[69][70][71][72][73]. Beatty et al [74] reported that the resistance of Campylobacter to erythromycin is increasing and varies between 12% and 95%.…”
Section: /7mentioning
confidence: 99%